COMMUNITY SUPPORTED AGRICULTURE – OPPORTUNITIES AND PERSPECTIVES - Corina, Ene (Economics of Agriculture, 2011)
This paper presents the concept of "Community Supported Agriculture" (CSA), aiming to underline its characteristics and advantages for all parties involved in the process. Creating such a partnership between farmers and consumers means more than just providing food on an established basis, but also helps small-scale farms and rural communities to better achieve their role, sharing benefts and risks with the consumers. Nowadays, CSA tends to be more and more an effective alternative for industrial agriculture approach, which promotes both sustainable development, food safety and nutritional balance in the same time.